Improved chosen-plaintext power analysis attack against SM4 at the round-output - Zhi-bo DU; Zhen WU; Min WANG; Jin-tao RAO (Tongxin xuebao)
The power analysis attack on SM4 using the chosen-plaintext method was proposed by Wang et al in 2013 CIS.The fixed data was introduced in the method when attacking the round key.However,the attack process was complex.There were many problems in the process,such as more power traces,more numbers of the chosen-plaintext and acquisition power traces.The correlation between the fixed data and the round key were presented,which could be used to decode the round key.Based on the correlation,the improved chosen-plaintext power analysis attack against SM4 at the round-output was proposed.The proposed method attacked the fixed data by analyzing the power traces of the special plaintext.And the round key was derived based on the correlation.The results show that the proposed attack algorithm is effective.The proposed method not only improves the efficiency of the attack by reducing number of power traces,number of the chosen-plaintext and number of acquisition power traces,but also can be applied to a chosen-plaintext power analysis attack against SM4 at the shift operation.